Total Electron Content Measurements in the Ionosphere Disturbed by High-Power High-Frequency Waves by the Methods of Incoherent Scattering of Radio Waves and Radio Sounding by Glonass Satellite Signal - Tereshchenko, E. D.; Cherniakov, S. M.; Yurik, R. Yu.; Rietveld, Michael T; Häggström, I. (Radiophysics and Quantum Electronics, 2020)
We present the results of comparing the total electron content measurements based on GLONASS satellite signals and the EISCAT UHF incoherent scatter radar (Tromsø, Norway) during modification of the high-latitude ionosphere in the magnetic zenith direction by high-frequency radio waves of the EISCAT/Heating facility (Tromsø, Norway). The measurements were performed during two experiment campaigns in October 2013 and in October 2018. In general, the total electron content variations obtained from the radar data in the altitude range 100–400 km were consistent with the total electron content variations from the GLONASS satellites. The efficiency of using GLONASS satellites for observations of high-latitude phenomena was shown. The anomalous increase in the total electron content by 4 TECU obtained from the incoherent scatter radar when the ionosphere was heated in the region close to the magnetic zenith is considered. The GLONASS satellite data show the total electron content reduction in the same region. To explain the disagreement between measurements by these two methods, the effect of smallscale electron-density irregularities arising in the region modified by high-power HF radio waves is considered. It is shown that when the electron density in artificial irregularities exceeds the background density of the medium by 2 · 10− 3 times in relative units, scattering by irregularities with spatial scales of the order of 16 cm becomes predominant in the reflected signal.